08 Ras-Association Domain Family 1 Isoform A (RASSF1A) is a Novel Regulator of TNF-alpha Signalling in Cardiomyocytes. (20th November 2012) - Mohamed, TMA; Zi, M; Maqsood, A; Prehar, S; Neyses, L; Oceandy, D
Abstract : Tumour necrosis factor-alpha; (TNF-alpha) plays key roles in the pathogenesis of heart failure. Cardiomyocytes express the TNF-alpha; receptor (TNFR), however, the mechanism of TNF-alpha; signal transmission in cardiomyocytes is not completely understood. Recent studies showed that in cancer cells TNFR is regulated by Ras-association domain family 1 isoformA (RASSF1A). Therefore, we investigated whether RASSF1A modulates TNF-alpha; signalling in cardiomyocytes. We used RASSF1A knockout (KO) mice and wild type (WT) controls and stimulated them with TNF-alpha; (10µg/kg i.v.). In WT mice acute treatment with low dose of TNF-alpha increased cardiac contractility and intracellular calcium transient amplitude, which is consistent with previously published data (Circulation 2004; 109:406-411). However, KO mice showed a blunted contractile response following acute TNF-alpha treatment as indicated by the change in end systolic elastance (in vivo) and intracellular calcium transient amplitude (isolated adult cardiomyocytes). We also found that RASSF1A formed a molecular complex with TNF-alpha; receptor in cardiomyocytes and this interaction was essential in the recruitment of TRADD and TRAF2, the major downstream effectors of TNF-alpha; signalling. By mapping the interaction domain we found that the C-terminal region of RASSF1A was responsible for the formation of TNF-alpha; receptor complex. Furthermore, using an adenoviral-mediate d shRNA construct we found that cardiomyocytes lacking RASSF1A exhibited reduced activation of NFkB, a downstream target of TNF-alpha. Overall, our data indicate an essential role of RASSF1A in regulating TNF-alpha; signalling in cardiomyocytes, with RASSF1A being key in the formation of TNF receptor complex and in the signal transmission to the downstream targets.